Evolución del gasto en infraestructura y su relación con la evolución del gasto total del Gobierno Regional de Loreto periodo 2019 – 2023 - Larrañaga Silva, Sara Lucia (2024)
This observational study with a quantitative approach and non-experimental correlational design investigates the relationship between infrastructure spending and the total expenditure of the regional government of Loreto during the period 2019-2023. The issue lies in the lack of specific investment in infrastructure acquisition, which limits regional expenditure growth and effectiveness, a crucial aspect for the sustainable development of the region. The general objective is to determine the relationship between the evolution of infrastructure spending and the total expenditure of the regional government. The results reveal a significant and positive relationship (r = 0.942, p = 0.017), suggesting that as infrastructure spending increases, so does the total regional expenditure, highlighting an interdependence in resource allocation and budget growth. A positive trend was identified in both types of spending throughout the study period, indicating a strategic approach in resource allocation for infrastructure development. However, there was no significant investment in infrastructure acquisition, implying a lack of correlation between this variable and total expenditure, highlighting a gap in the investment strategy. These findings underscore the importance of increasing investment in infrastructure acquisitions and improving project management to promote balanced and sustainable regional development. Optimizing the use of financial resources and reducing infrastructure gaps in Loreto are essential to improving the population's quality of life and promoting more inclusive and equitable economic growth.